ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK PADA MATERI TRIGONOMETRI - Fitrie Andayani; Wanda Anggeraeni Putri Solihin; Adiska Nadiyah Lathifah; Astriana Putri; Wahyu Hidayat (Journal on Education, 2019)
This study aims to determine students' mathematical problem solving abilities on trigonometry material. The population in this study were students of class X of Mahardhika Vocational School consisting of 33 X-1 graders majoring in Accounting and 33 X-3 Accounting students. The data analysis technique is done by giving a score on the students' answers to the test, presenting data, doing data verification, and drawing conclusions based on the analysis of the data obtained. Mathematical learning outcomes data in the form of posttest scores were analyzed using descriptive statistics and analytic statistics. The statistical test is the normality test, homogeneity test, t-test. The results of this study indicate that the results of student learning tests in the experimental class have an average value of 53.15 and the test results in the control class have an average value of 52.15. Based on the results of the t-test it can be seen from the significant data which is 0.873> 0.05 so that H0 is accepted. So that there is no significant difference between the experimental class students and the control class with mathematical problem solving skills in trigonometric material